LEGAL CHALLENGES IN WILDLIFE TRAFFICKING AND ITS IMPACT ON ZOONOTIC SPILLOVER - Manisha Naskar; Dr. Amrita Dasgupta (The Bioscan, 2026)
Aims: To critically analyze the interrelationship between wildlife trafficking and zoonotic spillover risk, evaluate the effectiveness of existing legal frameworks at international and national levels, and identify key legal and institutional gaps that hinder the prevention of emerging infectious diseases linked to wildlife trade. Methodology: A structured search of peer-reviewed articles and policy documents was conducted using Google Scholar, PubMed, and Science Direct, alongside reports from international organizations. Boolean search combinations included terms such as “wildlife trafficking” and “zoonotic spillover,” “illegal wildlife trade” and “public health risk,” and “wildlife trade legislation” and “disease emergence.” A thematic analysis approach was applied to synthesize findings from legal reviews, epidemiological studies, and governance reports. Themes examined included scale and mechanisms of wildlife trafficking, documented pathogen transmission events, strengths and weaknesses of regulatory frameworks, enforcement capacity, and recent One Health initiatives integrating environmental and public health governance. Results: The review indicates that approximately 6,000 species are affected annually by illegal wildlife trade across more than 160 countries, with an estimated global value of up to US20 billion per year. Nearly 70% of emerging infectious diseases in humans are zoonotic in origin, and at least 240 documented pathogen cases between 1990 and 2020 were directly linked to illegal wildlife trade. Mammals constituted the highest proportion of zoonotic hosts. Key legal gaps include inconsistent national penalties, limited enforcement capacity, weak cross-border cooperation, absence of mandatory pathogen screening in trade chains, and fragmented coordination between wildlife and public health authorities. Post-pandemic reforms have strengthened certain national regulations; however, implementation remains uneven and largely conservation-focused rather than health- integrated. Conclusion: Wildlife trafficking represents both a biodiversity crisis and a significant global health threat. Current legal frameworks inadequately integrate public health considerations into wildlife trade regulation. Strengthening enforcement capacity, harmonizing international penalties, embedding pathogen surveillance within trade controls, and operationalizing One Health principles are essential to reduce future zoonotic spillover risk.